MusykilÄt al-ThullÄb fÄ« al-Taâ€™aâ€™llum al-Lughat al-â€˜Arabiyyah wa Muá¸¥ÄwalÄt al-MudarrisÄ«n Liá¸¥illihÄ li al-Fashl al-Iâ€™dÄdi bi JÄmiâ€™ah DÄr al-SalÄm Gontor Ponorogo - Ulum, M. Miftahul; Fikri, Naufal (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2021)
Matriculation Language Programme is an intensive language programme that was first started on 2016 at university of Darussalam Gontor, under University Of Darussalam Gontor Language Center. This programme is to prepare new students without fluency in English and Arabic language. Especially for English and Arabic tests, it is also crucial for thesis writing,as University of Darussalam Gontor require Arabic and English for thesis writing. The objectives of this study are: (1) to find students' problems in learning Arabic programmed UNIDA Matriculation in the academic year 2019-2020 M (2) to find out the teacher's efforts in providing solutions to these problems in the UNIDA Matriculation program in the 2019-2020 academic year.This research is a qualitative descriptive study. From the data analyzed by the researchers found that: (1) Problems of learning Arabic students caused by the following factors: a) many students who participated in non-linguistic activities at UNIDA b) lack of enthusiasm and encouragement from individual students in learning Arabic c) students have not consider the importance of this program so that some of them blurred d) the lack of providing guidance and good advice to students about the importance of learning Arabic e) They consider themselves students, so do not want to be regulated in learning Arabic. (2) Teachers' efforts in providing solutions to solve these problems are: a) emphasizing the rules of language with a place that is set with a special boarding system so as not to speak with those who do not speak Arabic. b) watching Arabic films and discussions and giving praise, gifts for students who are active in this program. c) Teachers must be good examples in speaking Arabic and teaching them, so students can get used to it. d) make a meeting after the natural language skills training advises the language. e) make language activities such as competitions, quarantine, games, and quarantine in Arabic. Based on the results of this study it is expected that the program and community related to students, especially Arabic Language teachers, pay attention to students' motivation in speaking Arabic, and act and function according to their respective roles and functions. So students are motivated to learn Arabic and can practice Arabic in their daily lives.